GPSS interactive learning environment - Villarreal, Gonzalo Luján (2013)
This work presents an open source web environment to learn GPSS language in Modeling and Simulation courses. With this environment, students build their models by selecting entities and configuring them instead of programming GPSS codes from scratch. Teachers can also create models so that students can apply, analyze and interpret results. Thus, it includes a simulation engine that stores snapshots of models as they are executed, and allows students to navigate through these snapshots. The environment may be combined with existing learning management systems.